Nature of rights, validified by without document securities - Саванець, Л. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article is devoted to the issue of the legal nature of rights of uncertificated securities, their normativeand theoretical determinations are analysed. The author makes proposals as to perfection of current legislation of Ukraine of circulation of the uncertificated securities.